Implementasi Hidden Curriculum Dalam Pembentukan Karakter Siswa di SMP Muhammadiyah 1 Seyegan Yogyakarta - Ambar Wati Ningsih (Simpati, 2024)
This research is motivated by the fact that the curriculum used in schools is not yet optimal. There are still many student behaviors that tend to be selfish and show an attitude of not caring. This research aims to determine the character of Muhammadiyah 1 Seyegan Middle School students through the hidden curriculum that is applied. This research method uses a qualitative type and descriptive approach taking the background of Muhammadiyah 1 Seyegan Middle School. The results of the research show that the form of hidden curriculum implemented at SMP Muhammadiyah 1 Seyegan consists of spiritual and social aspects which include 5S culture (smile, greeting, greeting, politeness), morning tadarus, routine infaq, congregational prayer, memorizing surahs, reading write the Koran, reading corner and blessed Friday. The implication of the hidden curriculum is to instill in students religious character, discipline and responsibility. Supporting factors include teacher example, teacher motivation and parental support. The inhibiting factors are yourself and your peers.